Imperial luxury [videorecording] - Barrat, James; Grant, Eleanor; Janse, Andre; Kaptijn, Ellen; Luicita, Mary Ellen; McDonald, Jack; Obberse, Ton; Schorsevers, Martijn; Schot, Frank; Van Oosten, Ageeth; Verkerk, Mark (Great Palaces of the World, 1995)
Built on water one thousand years ago, the Doges Palace of Venice once ruled the Mediterranian and imprisoned Casanova. In Istanbul, Topkapi Palace became the capital of Ottoman intrigue, where hundreds of concubines vied for power, and brother killed brother to keep it. In Morocco, a sultan unknown in Europe built a palace to rival Versailles, the Royal Palace of Meknes. From the Royal Palace of Sintra, on the edte of the known world, a Portuguese prince led Europe into the great age of discovery.